2016
DOI: 10.1111/jocd.12201
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of two formulations containing diacetyl boldine, TGFβ1 biomimetic oligopeptide‐68 with other hypopigmenting/exfoliating agents and sunscreen provides effective and convenient treatment for facial melasma. Either is equal to or is better than 4% hydroquinone on normal skin

Abstract: Combination of DAB serum at night and DAB/TGF-β1 biomimetic oligopeptide-68/sunscreen cream in the morning and at noon was effective and safe for facial melasma. They were superior to HQ in pigment reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Melanosomes containing melanin pigments are transported to the neighboring keratinocytes . One study suggests that diacetyl boldine serum and DAB/TGF‐b1 biomimetic oligopeptide‐68/sunscreen cream use was effective and safe for facial melasma . From our in vitro and 3D spheroid coculture studies, we identified caprylic/capric triglyceride and diacetyl boldine (active B) as a single active to significantly inhibit melanin production and melanin synthesis through regulation of MITF gene expression in melanocytes (Figure A‐D).…”
Section: Discussionmentioning
confidence: 91%
“…Melanosomes containing melanin pigments are transported to the neighboring keratinocytes . One study suggests that diacetyl boldine serum and DAB/TGF‐b1 biomimetic oligopeptide‐68/sunscreen cream use was effective and safe for facial melasma . From our in vitro and 3D spheroid coculture studies, we identified caprylic/capric triglyceride and diacetyl boldine (active B) as a single active to significantly inhibit melanin production and melanin synthesis through regulation of MITF gene expression in melanocytes (Figure A‐D).…”
Section: Discussionmentioning
confidence: 91%
“…1,20 However, a study revealed that the value of SPF is not essential in terms of the sufficient amount and frequency of application of the sunscreen. 21 In our study, the most common reason behind not using sunscreen was the high cost followed by numerous side effects of these products. Alqarqaz et al 18 reported similar findings.…”
Section: Ta B L E 1 Demographic Characteristics Of Study Participantsmentioning
confidence: 67%
“…Furthermore, some studies reported that a sunscreen of SPF of at least 30 or more is recommended for good protection against sunlight 1,20 . However, a study revealed that the value of SPF is not essential in terms of the sufficient amount and frequency of application of the sunscreen 21 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2.6% of subjects had a significant improvement, 76.3% had a modest improvement, and 21.1% had a slight improvement. Each formulation was shown to be more effective than hydroquinone or to work faster in reducing pigmentation [ 102 ]. Revitol's product “Skin Brightener” contains Lumiskin with some patented ingredients, namely diacetyl boldine, that affect the expression of tyrosinase [ 11 ].…”
Section: Natural Products As Skin Whitening Agentsmentioning
confidence: 99%